1996
DOI: 10.1128/iai.64.9.3800-3810.1996
|View full text |Cite
|
Sign up to set email alerts
|

Gastric invasion by Trypanosoma cruzi and induction of protective mucosal immune responses

Abstract: Trypanosoma cruzi is an intracellular parasite transmitted from a reduviid insect vector to humans by exposure of mucosal surfaces to infected insect excreta. We have used an oral challenge murine model that mimics vector-borne transmission to study T. cruzi mucosal infection. Although gastric secretions have microbicidal activity against most infectious pathogens, we demonstrate that T. cruzi can invade and replicate in the gastric mucosal epithelium. In addition, gastric mucosal invasion appears to be the un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
39
0
3

Year Published

2008
2008
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 79 publications
(44 citation statements)
references
References 51 publications
(39 reference statements)
2
39
0
3
Order By: Relevance
“…The primary site of parasite entry in oral infection is still unknown. Previous data proved that in orally infected mice, parasites are not detected within the oropharynx and esophagus, instead, amastigote nests are present in the stomach [ 23 ]. In line with these findings, another group suggested that parasite glycoproteins, such as gp82 and gp30, are involved in gastric invasion following intragastric/intrapharyngeal inoculation [ 27 , 37 , 42 , 43 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The primary site of parasite entry in oral infection is still unknown. Previous data proved that in orally infected mice, parasites are not detected within the oropharynx and esophagus, instead, amastigote nests are present in the stomach [ 23 ]. In line with these findings, another group suggested that parasite glycoproteins, such as gp82 and gp30, are involved in gastric invasion following intragastric/intrapharyngeal inoculation [ 27 , 37 , 42 , 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…These models of oral T . cruzi infections result in parasitemia and heart parasitism, which indicates systemic infection [ 22 , 23 , 24 , 25 , 26 ]. In addition, T .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…31,32 In addition, it was recently observed that the gastric juice improves the infective potential of the parasite. 33,34 Indeed, infection by the oral route may better explain infection of predators (top of food webs) rather than skin contamination with infected feces of triatomines in the often dense animal fur. This is also probably the case with primitive hunting communities that were recognized consumers of raw meat 35 and probably were not very concerned about washing hands or foodstuffs.…”
Section: Discussionmentioning
confidence: 99%